A Programmatic Response, Including Bamlanivimab or Casirivimab-imdevimab Administration, Reduces Hospitalization and Death in COVID-19 Positive Abdominal Transplant Recipients. Issue 2 (February 2022) - Ahearn, Aaron J.; Thin Maw, Thin; Mehta, Rishi; Emamaullee, Juliet; Kim, Jim; Blodget, Emily; Kahn, Jeffrey; Sher, Linda; Genyk, Yuri
Abstract : Background: (COVID-19) has resulted in significant morbidity and mortality in solid organ transplant recipients. In December 2020, at the peak of the Los Angeles outbreak, our center rapidly implemented a protocol to improve outpatient management and provide bamlanivimab or casirivimab-imdevimab [COVID monoclonal antibody (mAb) therapies] to all eligible COVID-19 positive liver and kidney transplant recipients. Methods: A retrospective review of all abdominal organ transplant recipients who were COVID-19 polymerase chain reaction positive between February 2020 and February 2021 from our center was performed. Patient demographics, COVID-19 treatments, hospitalizations, and survival were reviewed. Patients were considered eligible for COVID mAb therapy if they met outpatient criteria at the time of diagnosis. Results: In the study period, 121 patients in the kidney transplant recipients group (KG) and 105 patients in the liver or combined liver/kidney transplant recipients group (LG) were COVID-19 polymerase chain reaction positive. Hospitalization rates were similar for the KG (45%) versus LG (35%) ( P = 0.20), but mortality was higher for the KG (22%) when compared to LG (10%) ( P = 0.02). Our programmatic response, including outpatient COVID mAb therapies, reduced hospitalizations ( P = 0.01) and deaths ( P = 0.01). Ninety-four KG and 87 LG patients were identified as potentially eligible for COVID mAb therapy, and 17 KG and 17 LG patients were treated. COVID mAb therapies reduced hospitalization from 32% to 15% ( P = 0.045) and eliminated mortality (13% versus 0%, P = 0.04). Conclusions: An aggressive approach including outpatient COVID mAb therapy in the COVID positive abdominal organ transplant recipients significantly decreased hospitalization and death. Early outpatient intervention for COVID-19 disease in transplant patients should be considered where possible.